Analysis of dynamic changes in the urbanization of Xixian National New Area and its driving forces. Issue 9 (November 2019) - Chang, Yue; Hou, Kang; Li, Xuxiang; Zhang, Yue
This study analysed the dynamic changes and driving forces in the urbanization from 1997 to 2016 of Xixian, a national new development area in Xi'an City, by using geographical information systems and remote sensing. The results showed that farmland was the main land use type from 1997 to 2004. However, the construction land occupied the largest area from 2011 to 2016. There was a significant expansion in the construction land area (33.24%), unused land (91.10%) and woodland (37.59%) from 1997 to 2016. In addition, in the period from 1997 to 2016, the water body, grassland and farmland were reduced by 52.52%, 31.73% and 23.84%, respectively. The increasing area of construction land was the inevitable result of urbanization. The terrain, policy and geographical location factors are the main driving forces for changes in the land use and urbanization. The planning of Xixian National New Area's building environment should be linked and connected with the Xi'an main districts. The findings confirmed the applicability and effectiveness of the combined method of geographical information systems and remote sensing for revealing the notable spatio-temporal features in the dynamic changes in the land use and land cover throughout different time periods of Xixian.